2014
DOI: 10.1039/c4nr04864d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous titania based yolk–shell nanoparticles as multifunctional theranostic platforms for SERS imaging and chemo-photothermal treatment

Abstract: Recently surface-enhanced Raman scattering (SERS) imaging guided theranostic nanoplatforms have attracted considerable attention. Herein, we developed novel yolk-shell gold nanorod@void@meso-porous titania nanoparticles (AuNR@void@mTiO 2 NPs) for simultaneous SERS imaging and chemophotothermal therapy. Our work showed three highlighted features: first, we proposed a facile and versatile "up to down" SERS labeling strategy for the drug delivery system, in which "empty carriers" were presynthesized, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 38 publications
0
65
0
1
Order By: Relevance
“…The above results demonstrated that the PPY@PAA/fmSiO 2 NPs have superior ability of NIR photothermal transduction, which are promising as PTT candidates to enhance the therapeutice fficacy.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The above results demonstrated that the PPY@PAA/fmSiO 2 NPs have superior ability of NIR photothermal transduction, which are promising as PTT candidates to enhance the therapeutice fficacy.…”
Section: Resultsmentioning
confidence: 88%
“…[2][3][4] Upon NIR light irradiation, the heat generated from thesen anomaterials not only leads to thermala blation of morbid position withoutd amaging normal tissues but also triggerst he release of drug molecules from the nanocarriers inside cells. [5] Ag eneral route to developm ultifunctional photothermal agents is presented to achieve the optimal therapy effect.…”
Section: Introductionmentioning
confidence: 99%
“…To verify the elastic property of the mSiO 2 shell, H 2 O 2 was used for selective dissolution of the Ag coating. Au@ AgNR@mSiO 2 NPs prepared with 150 μL of AgNO 3 were dispersed in 1 mL of water, followed by the addition of different volumes (20,50, and 100 μL) of H 2 O 2 solution (30%, v/v). The reaction was allowed to proceed at room temperature, and the reaction rate was evaluated by monitoring the absorption spectra evolution of the solutions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The new nano-carriers that have rapidly emerged as drug delivery systems may overcome these limitations. [30][31][32][33][34][35][36][37][38] The drug delivery mechanism of nano-carriers depends on enhanced permeability and retention (EPR) effects. The anticancer drugs are either conjugated to the nano-carriers or packaged as nanocapsules.…”
Section: Jaebum Choomentioning
confidence: 99%